MOBILE APPLICATION DESIGN FOR PROCUREMENT ON XYZ COMPANY - Sugianto, Victoria Angela; Suyoto, Suyoto; Rahayu, Swahesti Puspita (Jurnal Teknik Informatika (Jutif), 2023)
Procurement of goods in Indonesia continues to experience rapid growth. In 2022, the Indonesian government has allocated a budget of Rp. 2,714 trillion to fulfill government spending. Procurement of goods is almost carried out every month, to meet office needs and support operational facilities. Document storage is one of the important things in every company, however, until now there is no mobile application that can help archiving documents online. This is a problem where files are created and stored manually, so it is still difficult to find files and in transparating data. From the existing problems, there needs to be an innovation that can facilitate the process of managing and storing matching files. One of the innovations was carried out by designing a mobile application using the Design Thinking method. The Design Thinking method can be used to solve problems by rearranging problems into user perspectives that produce design ideas. The results of this study are in the form of a procurement mobile application design. It is hoped that the design and development of the mobile application will be able to provide convenience for Company XYZ in storing procurement documents. So that procurement can be done appropriately, effectively, efficiently, and the procurement documentation process can be carried out quickly.